A system dynamics perspective on the willingness of freight receivers to pay for city hubs - Claudia Andruetto; Henrik Gillström (Cleaner Logistics and Supply Chain)
Through consolidation, city hubs offer potential solutions to sustainability challenges in urban freight systems. However, the viability of such hubs has been questioned, as the willingness to pay of businesses receiving goods has been an issue. This study employs a system dynamics approach to explore this willingness to pay in consolidation initiatives by quantifying the benefits receivers can gain, thus bridging a gap in the literature. The system dynamics method allows a holistic view of the system. Therefore, a quantitative model is built to explore the behaviour of the businesses receiving goods and their interests in value-added services. Data from a case study in Stockholm is used as quantitative input. Moreover, fourteen businesses in the area are interviewed to understand their needs and to create different scenarios. The analysis of the interviews reveals that the level of interest in value-added services varies depending on the type of business. Four types of receivers are identified: large offices, small offices, large shops, and small shops. The model results show that the main benefits for the receivers are time savings in handling deliveries, leading to cost savings and the use of the city hub for storage. The results of this research can be used by decision-makers in the private and public sectors to understand the dynamics of city hubs and to formulate effective policies for the success of these hubs. The originality of this study lies in the combination of the system dynamic approach and the receivers’ perspective, which is relatively underexplored. The results can thus provide valuable insights in achieving viable consolidation solutions.